Development and Application of Specific Cytokine Assays in Tissue Samples from a Bottlenose Dolphin with Hyperinsulinemia - Eberle, Kirsten; Waters, Theresa; Jensen, Eric; Venn-Watson, Stephanie; Sacco, Randy E. (Frontiers in Endocrinology, 2013)
Chronic inflammation has been associated with insulin resistance and type 2 diabetes (T2D) in humans. Postmortem hepatic and splenic tissue from a 46-year-old geriatric male bottlenose dolphin (Tursiops truncatus) with insulin resistance (chronic hyperinsulinemia with hyperglycemia), chronic inflammation (white blood cell count greater than 12,000 cells/μL), and mild fatty liver disease was evaluated for elevated pro-inflammatory mediators. Cytokine mRNA expression in postmortem hepatic and splenic tissue, as determined by real-time PCR, included an array of cytokines: TGF-β, TNF-α, IFN-γ, IL-2, IL-4, IL-10, IL-12p40, IL-13, and IL-18. Values from this dolphin were compared to a younger reference dolphin with no known chronic metabolic perturbations or inflammation. Levels of TGF-β, TNF-α, and IL-4 were higher in the case dolphin's liver compared to that of the reference dolphin. In the case dolphin's spleen, IL-10 and IFN-γ mRNA was upregulated while IL-4 was less than reference dolphin. IL-18 and IL-13 were upregulated in both tissues. Fluorescent immunohistochemistry (IHC) utilized the following antibodies: anti-porcine IL-6, anti-bovine IFN-γ, IL-4, and IL-10, anti-human TGF-β, anti-ovine IL-1β, and anti-dolphin IL-8. Fluorescent IHC in spleen from the case dolphin revealed staining of IL-4, IL-6, IL-8, and TGF-β throughout the tissue. IL-10 and IFN-γ were seen to predominate in areas surrounding the follicles of splenic tissue. This is the first characterization of cytokine levels in dolphin hepatic and splenic tissue. While there are limitations to a case study, this report of inflammatory biomarkers in tissues of a dolphin with insulin resistance and fatty liver disease are similar to those observed in human patients.